Penerapan Model Pembelajaran Student Facilitator And Explaining Untuk Meningkatkan Motivasi Belajar Kelas IV Paringgonan - Nurhayati Siregar; Irmasari Daulay; Ratih Amaeini Hasibuan (UIR Press, 2023)
This study aims to increase student learning motivation. By using the student facilitator and explaining learning model in grade IV Paringgonan. The type of research used is classroom action research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation, and reflection. This research was conducted at SD Negeri 0614 Paringgonan. The subjects of this study were grade IV students of SD Negeri 0614 Paringgonan with a total of 20 students. Data collection techniques are carried out using observation and questionnaires and documentation. The data analysis techniques used are carried out descriptively, qualitatively and quantitatively. Student learning motivation in science subjects using the student facilitator and explaining learning model shows an increase. In the pre-cycle the percentage of student motivation is still in the less category (57%). In the first cycle, it has increased, so it rises to the sufficient category (74%). With the final result of students' science learning motivation in the very good category (89%). So it can be proven that the student facilitator and explaining learning model can improve student learning outcomes in science subjects in grade IV Paringgonan